Analisa Kandungan Merkuri (Hg) Di Wilayah Penambangan Emas Danau Payawan Desa Tumbang Panggo Kecamatan Tasik Payawan Kabupaten Katingan - Fahrul Indrajaya; Lisa Virgiyanti (PROMINE, 2019)
Field activities conducted to determine the level of mercury content in the water flow of Lake Payawan,Tumbang Panggo Village, Tasik Payawan District, Katingan Regency, Central Kalimantan Provincebased on laboratory test results to obtain the results of mercury content in upstream to downstream ofLake Payawan. From this research, it is necessary to test the quality of water in the laboratory in orderto analyze the water quality parameters so it can be known mercury content (Hg) in Lake Payawanwater flow. From the test results on 6 points river water samples in the laboratory of the IndustrialResearch and Standardization Center of Banjarbaru City showed the highest mercury content found insample number 3 with P. 2076 test code taken at the location of the middle Lake Payawan TasikPayawan District with mercury levels located At a rate of 0.069 μg / l or 0.000069 mg / l, this reflectsthe presence of other factors that may also affect the level of mercury content in Lake Payawan flow.